Pengaruh Kualitas Layanan One Day Sercive dan Fasilitas pada Penerimaan Mahasiswa Baru terhadap Kepuasan Calon Mahasiswa - Ermini Ermini; Dina Sri Nindiati; Muhammad Najib (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research was conducted to find out The Influence of One Day Service (ODS) Service Quality and PMB Facilities on the Satisfaction of Prospective Students in 2022 at PGRI University Palembang. The data collection method used to obtain data in this research is field research. Namely, research is carried out directly by distributing questionnaires to respondents deemed to meet the requirements. The primary data source used was primary data collected through questionnaires distributed to respondents. This questionnaire measures the quality of one-day service (ODS), PMB facilities, and prospective student satisfaction. The research results based on data processing with the help of the SPSS version 26 for window program, obtained simultaneous results (F Test) showed that Fcount was 72.307 > Ftable 3.10 with a significant level of 0.000 < 0.05, so it can be concluded that there is an influence between the quality of one day service (ODS) (X1) and PMB facilities (X2) together (simultaneously) on prospective student satisfaction (Y). And the coefficient of determination results show that the R2 value is 0.611, which means 61.1%. The one-day service (ODS) service quality variable and the PMB facility variable can be explained, while 38.9% (100% - 61.1%) is influenced by other variables not studied. Conclusion, There is an influence between the quality of One Day Service (ODS) (X1) and PMB facilities (X2) together (simultaneously) on prospective student satisfaction (Y), Keywords: one day service (ODS) service quality, PMB facilities, prospective student satisfaction